Dietary fibre : chemical and biological aspects - Southgate, D. A. T. (Woodhead Publishing in food science, technology, and nutrition., 2009)
Advances made in the last two decades have provided increasing insights into the chemical complexity of dietary fibre and this important book reviews the current state of knowledge on the role of fibre in the diet. It covers such areas as the chemistry of dietary fibre, health benefits to the consumer, effects on the small and large intestine, effect on lipid metabolism, implications to the industry and more. Dietary fibre: Chemical and biological aspects will prove essential reading for food chemists and technologists, nutritionists, biological scientist, clinicians, the food pharmaceutical industries, and regulatory bodies.